Videos engaging in conspiracy theories: Promoting or refuting foreign-pseudohistory on the video-sharing website (Bilibili) - Yi Zhu; Yichao Wang; Siyuan Ma (PLoS ONE, 2025)
Foreign pseudohistory, as one format of conspiracy theories, is an unverified discourse explicitly stating that a culture, civilization, or achievement outside one’s homeland country did not exist, does not have historical continuity, or was plagiarized from this homeland country. The current study analyzed 302 videos about foreign pseudohistory from a popular Chinese video-sharing website (Bilibili) and found 213 videos supporting foreign pseudohistory and 89 videos opposing foreign pseudohistory. Videos opposing foreign pseudohistory attract more viewers and comments than videos supporting foreign pseudohistory, but the latter videos are posted by a smaller group of core creators and also attract considerable numbers of views. The inductive thematic analysis identified three major themes from these videos, including: 1) how foreign civilizations and history were based on fabrication and plagiarism; 2) promoting foreign pseudohistory as a way to fight against Western-centrism; and 3) refuting and mocking foreign pseudohistory and enlightening the public about the real history. The implications of this study were discussed